Evaluasi Rizobakteri Indigenous Gayo Lues sebagai PGPR Terhadap Pertumbuhan dan Hasil Nilam Aceh: Evaluation of Gayo Lues Indigenous Rhizobacteria as a PGPR on The Growth and Yield of Achenese Patchouli - Halimursyadah; Trisda Kurniawan; Marisa, Rika (Jurnal Hortikultura Indonesia, 2024)
Rhizobacteria are a group of microorganisms that actively and aggressively colonize the rhizosphere area and act as plant growth promoters. Patchouli (Pogostemon cablin Benth.) is one of the essential oil producing plants known as patchouli oil. This study aims to determine the interaction between the treatment of indigenous rhizobacterial isolate types with varieties on the growth and yield of Aceh patchouli plants. This research was conducted at the Laboratory of Seed Science and Technology, Department of Agrotechnology, Faculty of Agriculture and Nino Park, Syiah Kuala University, Darussalam, Banda Aceh, Aceh. This study used a 7x3 factorial pattern Randomized Group Design (RGD) with 3 replications. The factors studied were 7 types of rhizobacterial isolates (Without Rizobacteria, PG 5/1, PG 5/3 P, PG 6/2, PG 7/3 C, PG 8/1, and PG 9/2 C) and 3 types of patchouli varieties (Sidikalang, Lhokseumawe, and Tapak Tuan). The results showed a very significant interaction between rhizobacteria treatment and type of variety on the parameters of plant height 8 and 12 WAA, number of leaves 4, 8, and 12 WAA, number of branches 8 and 12 MSA, wet biomass weight, wind dry biomass weight, and significantly influenced the parameters of plant height and number of branches 4 WAA. The best growth and yield of Sidikalang variety using rhizobacterial isolate PG 9/2 C, Lhokseumawe variety using rhizobacterial isolate PG 6/2, and Tapak Tuan variety using rhizobacterial isolate PG 8/1 based on wind-dry biomass weight parameter.Keywords: Biofertilizer, Dry Biomass, Biostimulant